2011
DOI: 10.1007/s11431-011-4491-0
|View full text |Cite
|
Sign up to set email alerts
|

A constitutive model for granular materials considering grain breakage

Abstract: International audienceA particle breakage has a significant impact on the mechanical behavior of granular materials. In this paper, we present an elasto-plastic model with two yield surfaces to which the influence of particle breakage has been introduced. The main feature of this model is to incorporate the change in the critical state line (CSL) consequent to the grain breakage induced by isotropic and deviatoric stresses during loading. For this purpose we propose a breakage function which connects the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(41 citation statements)
references
References 24 publications
1
38
0
2
Order By: Relevance
“…Daouadji et al (2001), who proposed one of the first constitutive models that consider 74 the effect of breakage, based their investigation on the effect grain breakage has on the critical 75 state line. This observation was the basis for many other constitutive models (Russell and Khalili 76 2002;Hu et al 2011;Wood et al 2009). The framework proposed by Einav (2007b) is based on a 77 yielding condition that derives from the definition of Einav's breakage parameter (Einav 2007b), 78 coupled to some other hypotheses.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Daouadji et al (2001), who proposed one of the first constitutive models that consider 74 the effect of breakage, based their investigation on the effect grain breakage has on the critical 75 state line. This observation was the basis for many other constitutive models (Russell and Khalili 76 2002;Hu et al 2011;Wood et al 2009). The framework proposed by Einav (2007b) is based on a 77 yielding condition that derives from the definition of Einav's breakage parameter (Einav 2007b), 78 coupled to some other hypotheses.…”
mentioning
confidence: 82%
“…Breakage is introduced as a hardening parameter (Daouadji et al 2001;Einav 2007a;45 Wood et al 2009), or is calculated from the stress parameters that are computed independently 46 (Hu et al 2011). In addition, breakage is considered to be a plasticity indicator, and starts with the 47 onset of plasticity, which does not represent the reality of the phenomenon.…”
mentioning
confidence: 99%
“…Employing Eqs. (26) and (27), the thermal conductance H e of the rectangular sample of granular material with random packing structure can be expressed as.…”
Section: The Parallel-column Modelmentioning
confidence: 99%
“…The probability density function p(d) of the fractal distribution is formulated as [26] pðdÞ ¼ ð3 À aÞ d 2Àa…”
Section: Parameter Valuementioning
confidence: 99%
“…It is concluded that the reference crushing stress could be regarded as an effective index to evaluate the strength of granular material in triaxial compression tests. [11][12][13][14][15] to describe crushing behaviour for granular materials. Although most of them are capable of representing the variation in mechanical behaviour before and after particle crushing occurrence, less of them directly adopt the crushing stress in the specific expression of constitutive relation.…”
Section: Introductionmentioning
confidence: 99%